A new species of the earthworm genus Pheretima Kinberg, 1867 (Megascolecidae: Oligochaeta) from Vietnam - Kim Hoi, Huynh Thi; Thuan, Nguyen Van (Academia Journal of Biology, 2014)
A new species of the earthworm genus Pheretima Kinberg, 1867 (Megascolecidae: Oligochaeta) from Vietnam